Salviae miltiorrhizae and ligustrazine hydrochloride injection combined with mecobalamin for treating diabetic peripheral neuropathy: A protocol for systematic review and meta-analysis. Issue 3 (22nd January 2021) - Deng, Zhiyuan; Wang, Manjia; Fan, Yaohua; Liu, Min
Abstract: Objective: Currently, it is unclear whether the salviae miltiorrhizae (Danshen Salvia) and ligustrazine hydrochloride (Chuanxiong Chuanxiong) (SMLH) injection combined with mecobalamin can improve diabetic peripheral neuropathy (DPN). We conducted a systematic analysis to evaluate the clinical effects of SMLH injection combined with mecobalamin for treating DPN. Methods: Seven databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang Database (Wang Fang), Chinese Biomedical Literature Database (CBM), and VIP Database for Chinese Technical Periodicals (VIP) were searched for systematic literature retrieval. Each database was searched up to 2020 to identify randomized controlled trials on DPN treated with SMLH injection combined with mecobalamin. We used the RevMan 5.3 and Stata 14.0 software to assess the risk of bias in the included trials. Results: A total of 15 publications, including 1349 samples, were reviewed. The total effective rate of SMLH injection combined with mecobalamin was 31% higher than that of mecobalamin alone (95% confidence interval [CI] = 1.23–1.38; P  < .00001). The experimental group showed a significant increase in the motor conduction velocity (MCV) of the peroneal nerve (weighted mean difference [WMD] = 4.81, 95% CI 3.53–6.09; P  < .00001). In addition, SMLH injection combined with mecobalamin showed a statistical significant effect on the sensory conduction velocity (SCV) of the peroneal nerve (WMD = 5.03, 95% CI = 4.16–5.90; P  < .00001), and MCV of the median nerve (WMD = 5.38, 95% CI = 4.05–6.72; P  < .00001). The WMD for the change in SCV in the median nerve was 4.89 m/s (95% CI = 3.88–5.89; P  < .00001). The P -values of the Egger and Begg tests were 0.967 and 0.961, respectively, indicating no publication bias. Subgroup and sensitivity analyses indicated that the results for MCV and SCV of the peroneal nerve and the median nerve were stable. Conclusion: SMLH injection combined with mecobalamin can improve DPN, compared with mecobalamin alone.